IMPLEMENTATION OF THE PROJECT A3 METHODOLOGY TO SOLUTION THE LOSS OF PRODUCTIVITY IN THE PRODUCTION OF RASCHEL BAGS - Lopes, Thiago Teixeira; Regattieri, Carlo Roberto (Revista Interface Tecnológica, 2023)
This article presents the implementation of the Project A3 Methodology, which was applied in the Raschel knitted bag production sector of a textile company, located in the industrial district III in the city of Itápolis-SP. Faced with the competitive market we live in, more and more industries seek to apply methods and tools in which they can increase their production capacity, have excellence in product quality and reduce waste. In order to achieve the proposed objective of preparing an A3 Project, it was necessary to know and implement other tools in the production process. The tool used in this case was the OEE Indicator – Overall Equipment Effectiveness, where the Availability, Performance and Quality indices are demonstrated. With the detailing of process losses collected along with the production process, Project A3 was created with the objective of increasing productivity in the raschel sack sector. The elaboration of Project A3 was done by the production manager together with the company's OEE team.
Keywords: project A3.; productivity.; OEE.; availability.; performance.; quality.